The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s10346-015-0584-3
|View full text |Cite
|
Sign up to set email alerts
|

Lake outburst and debris flow disaster at Kedarnath, June 2013: hydrometeorological triggering and topographic predisposition

Abstract: Lake outburst and debris flow disaster at Kedarnath, June 2013: hydrometeorological triggering and topographic predisposition Abstract Heavy rainfall in June 2013 triggered flash flooding and landslides throughout the Indian Himalayan state of Uttarakhand, killing more than 6000 people. The vast majority of fatalities and destruction resulted directly from a lake outburst and debris flow disaster originating from above the village of Kedarnath on June 16 and 17. Here, we provide a systematic analysis of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
90
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(91 citation statements)
references
References 37 publications
1
90
0
Order By: Relevance
“…The expansion of existing lakes and formation of new lakes will increase the potential for mass movements of ice or rock to trigger GLOF events, and new GLOF paths will increase the downstream potentially affected land area. The Tehsil of Kullu (K), within the central District of Kullu is identified thousands of people has highlighted that extreme hydrometeorological conditions can trigger catastrophic GLOFs (Singh et al 2014;Allen et al 2015), yet knowledge on how such conditions may change in the future is limited by uncertainty in regional climate projections. Baseline information on permafrost distribution in the Kullu District has recently been established ), but ground temperature measurements and further field validation is required before the implications of thawing permafrost on GLOF stability can be reasonably quantified and integrated into a hazard assessment.…”
Section: Discussionmentioning
confidence: 99%
“…The expansion of existing lakes and formation of new lakes will increase the potential for mass movements of ice or rock to trigger GLOF events, and new GLOF paths will increase the downstream potentially affected land area. The Tehsil of Kullu (K), within the central District of Kullu is identified thousands of people has highlighted that extreme hydrometeorological conditions can trigger catastrophic GLOFs (Singh et al 2014;Allen et al 2015), yet knowledge on how such conditions may change in the future is limited by uncertainty in regional climate projections. Baseline information on permafrost distribution in the Kullu District has recently been established ), but ground temperature measurements and further field validation is required before the implications of thawing permafrost on GLOF stability can be reasonably quantified and integrated into a hazard assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to 9 June, there was no significant rainfall, but a discharge rate varied from 54 to 65 m 3 /s, suggestive of runoff from glacier and snowmelt. The satellite-based imageries indicated that, in winter 2013, there was increase in snowfall of 30% in the Alaknanda and Mandakini catchment area [59,60]. Previous studies reported that the extreme rainfall in June has caused an acceleration of snowmelt-runoff and accumulation of large volume of water in the Lake [52,61].…”
Section: Resultsmentioning
confidence: 99%
“…Torrential rains rapidly raised the water level of the moraine-dammed Chorabari Lake, Uttarakhand, India, in June 2013. The dam breached and released 400 000 m 3 of water into the already flooded Mandakini River, inundating the pilgrimage city of Kedarnath (Allen et al 2015), and severely damaging at least two HPP sites downstream (Sandrp 2013). The recognition that GLOFs can substantially exceed design floods of HPP at the risk of damage or complete inoperability (Richardson and Reynolds 2000) hinges on a handful of case studies, but the regional picture of GLOF exposure remains illdefined.…”
Section: Introductionmentioning
confidence: 99%